2004
DOI: 10.1001/archpsyc.61.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Volumes in Schizophrenic Twins

Abstract: Although hippocampal volume in healthy individuals is largely affected by genetic factors, it is subject to substantially greater modulation by environmental factors in schizophrenic patients and their relatives. The results are discussed in view of assumptions underlying classic twin methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(67 citation statements)
references
References 47 publications
7
59
1
Order By: Relevance
“…However, shared environmental factors could nonetheless have a nonnegligible contribution to abnormalities observed within particular cerebral structures. Using variance components analysis, hippocampal volume was in fact found to be substantially influenced by unique and shared environmental factors in schizophrenia subjects and their nonpsychotic twins, whereas additive genetic effects dominated in healthy twin pairs (van Erp et al, 2004). We are not aware of any twin studies that have used similar analytic techniques in the thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…However, shared environmental factors could nonetheless have a nonnegligible contribution to abnormalities observed within particular cerebral structures. Using variance components analysis, hippocampal volume was in fact found to be substantially influenced by unique and shared environmental factors in schizophrenia subjects and their nonpsychotic twins, whereas additive genetic effects dominated in healthy twin pairs (van Erp et al, 2004). We are not aware of any twin studies that have used similar analytic techniques in the thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) studies in unaffected family members (FM) of schizophrenia patients suggest that genetic factors affect brain structure (1)(2)(3)(4)(5), with FM generally showing characteristics of brain structure in-between patients and healthy controls (HC). Likewise, high risk individuals such as patient offsprings with no clinical history of psychosis, have similar structural abnormalities, most notably in hippocampus and amygdala, with some contradictory results (6-9) having being reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…This study also reported that both MZ and DZ discordant twins have smaller whole-brain, parahippocampal, and hippocampal volumes than healthy twins, and that affected twins have yet smaller whole-brain volumes than their non-schizophrenic co-twins. The hippocampal size findings were replicated in a Finnish twin study [van Erp et al, 2004]. Together, these observations indicate the presence of a genetic influence on brain volumes, but the additional reduction in whole-brain volume observed in the affected compared to the unaffected co-twins dynamic interaction between DNA sequence, epigenetic DNA modifications, environment, gene expression, and environmental factors that all combine to influence phenotype.…”
Section: Classical Twin Study Designs: Genes and Environmentmentioning
confidence: 68%